From the Children's Oncology Group: Evidence-Based Recommendations for PEG-Asparaginase Nurse Monitoring, Hypersensitivity Reaction Management, and Patient/Family Education. (November 2017) - Woods, Deborah; Winchester, Kari; Towerman, Alison; Gettinger, Katie; Carey, Christina; Timmermann, Karen; Langley, Rachel; Browne, Emily
PEG-aspariginase is a backbone chemotherapy agent in pediatric acute lymphoblastic leukemia and in some non-Hodgkin lymphoma therapies. Nurses lack standardized guidelines for monitoring patients receiving PEG-asparaginase and for educating patients/families about hypersensitivity reaction risks. An electronic search of 6 databases using publication years 2000-2015 and multiple professional organizations and clinical resources was conducted. Evidence sources were reviewed for topic applicability. Each of the final 23 sources was appraised by 2 team members. The GRADE (Grading of Recommendations Assessment, Development and Evaluation) system was used to assign a quality and strength rating for each recommendation. Multiple recommendations were developed: 4 relating to nurse monitoring of patients during and after drug administration, 8 guiding hypersensitivity reaction management, and 4 concerning patient/family educational content. These strong recommendations were based on moderate, low, or very-low-quality evidence. Several recommendations relied on generalized drug hypersensitivity guidelines. Additional research is needed to safely guide PEG-asparaginase monitoring, hypersensitivity reaction management, and patient/family education. Nurses administering PEG-asparaginase play a critical role in the early identification and management of hypersensitivity reactions.